INSOMNIA IN OLDER ADULT: A CASE REPORT (Journal of Pharmaceutical Negative Results, 2023)
Sleep problems are common in the elderly population.Epidemiological analysis have shown that 30%–60% of all older persons have one or more sleep complaint, including difficulty falling asleep, problems staying asleep at night or falling back asleep after awakening, early morning awakenings, extreme daytime sleepiness, and daytime exhaustion.(1) Insomnia is a critical problem which is characterised by having a hard time initiating sleep,besieged to maintain sleep, waking up frequently during the night, be liable to wake up too early and are unable to go back to sleep, sleep is non-restorative or of poor quality.(2) It affects the quality of life and health status of a person. It is no longer just an appendage of psychiatric disease in that increasing substantiation supports that insomnia is associated with medical problems such as increased cardiovascular risks.(3) Sleep disturbances increase with age. Total sleep time and sleep competence (i.e., the percent of time spent sleeping when lying in bed) decreases and the time awake after sleep onset increases during middle age, and sleep efficiency continues to decrease amongst older adults. Older adults also experience changes in their circadian cycle, with earlier bed and wake times.